Cartap hydrochloride poisoning: a case report - Raj, Sumesh; S., Sheetal (International Journal of Research in Medical Sciences, 2017)
Cartap hydrochloride is a thiocarbamate insecticide used for control of chewing and sucking insects of all stages of development, on many crops. It is an analogue of nereistoxin. Poisoning with cartap is very rarely reported from India. We report a 46 year old man who consumed cartap with alcohol, presented with nausea & vomiting and improved with supportive measures.